Event- and time-based prospective memory in hemodialysis patients. Issue 1 (1st January 2020) - Wang, Bin; Li, Mengting; Tang, Fang; Wang, Yue; Han, Yuchen; Lu, Wen; Zhang, Lan; Zhang, Ling; Ni, Weijie; Zhang, Li; Zhang, Liuping
Abstract: Objective: The present study investigated whether hemodialysis (HD) patients exhibit future memory impairment (PM; the capability of remembering to perform expected future actions) and exploring relevant factors of PM task performance. Methods: Sixty HD patients and 60 healthy controls matched by age are enrolled in the Mini-Mental State Examination (MMSE), Finger Span Test (DST), Oral Fluency Test (VFT), Ray Auditory Oral Learning Test (RAVLT), Received Stroop Color Word Interference Test (SCWT), and event-based PM (EBPM) and time-based PM (TBPM). Results: There were no significant difference between the patients and controls in the DST-Forward digit span (9.00 ± 1.25 versus 8.97 ± 1.33, p = 0.96), the DST-Backward digit span (5.23 ± 1.98 versus. 4.60 ± 1.65, p = 0.11), the RAVLT of delayed recall (7.28 ± 2.36 versus 6.87 ± 3.33, p = 0.09) and the VFT for animals (16.70 ± 3.50 versus 17.68 ± 5.45, p = 0.56). By comparison, patients had a much worse performance than controls on the MMSE (29.10 ± 0.84 versus 28.33 ± 0.77, p < 0.001), the RAVLT of total recall (44.47 ± 5.82 versus 40.03 ± 10.46, p < 0.001) and delayed recognition (6.93 ± 1.49 versus 5.4 ± 1.33, p < 0.001), the SCWT reaction time in reading (6.47 ± 1.05 versus 7.47 ± 1.86, p < 0.001), color naming (9.07 ± 1.29 versus 11.43 ± 2.34, p < 0.001), interference (8.78 ± 1.92 versus 10.22 ± 2.91, p < 0.001) and inhibition/switching (14.53 ± 2.90 versus 19.85 ± 4.69, p < 0.001), the VFT for fruit (17.47 ± 3.18 versus 15.92 ± 4.56, p < 0.001), the EBPM task (7.85 ± 0.40 versus 7.08 ± 1.43, p = 0.01), and the TBPM task (3.30 ± 1.31 versus 2.26 ± 1.82, p < 0.001). Conclusions: Our results suggest that EBPM and TBPM are impaired in HD patients and that PM may be applied to help evaluate cognitive dysfunction in HD patients.